Structural characterization and anti-inflammatory activity of a novel polysaccharide PKP2-1 from Polygonatum kingianum - Wang, Zhen; Liu, Hui; Fu, Ranze; Ou, Jinmei; Wang, Bin (Frontiers in Nutrition, 2023)
In this study, we isolated a novel polysaccharide, PKP2-1, from rhizomes of Polygonatum kingianum Coll. & Hemsl. for the first time, which was then successively purified through hot-water extraction, 80% alcohol precipitation, anion exchange and gel permeation chromatography. Monosaccharide composition assay revealed that PKP2-1 was mainly composed of glucose, galactose, mannose and glucuronic acid at an approximate molar ratio of 6:2:2:1. It had a molecular weight of approximately 17.34 kDa. Structural investigation revealed that the backbone of PKP2-1 consisted of →2, 3)-α-D-Galp(4→, →2)-α-D-Manp(3→, →2)-β-D-Glcp(4→ and α-D-Glcp(3→ residues with side chains →2)-β-D-Glcp(4→, →1)-α-D-Galp(4→ and α-D-Glcp(3→ branches located at O-3 position of →2, 3)-α-D-Galp(4→. The in vitro anti-inflammatory activity of PKP2-1 in MH7A cells was assessed using a CCK-8 kit assay, which showed that PKP2-1 could reduce the expression of IL-1β and IL-6, increase the expression of IL-10 and induce apoptosis of synovial fibroblasts, suggesting that PKP2-1 could inhibit MH7A cell growth and potentially be exploited as an anti-inflammatory agent.